The Mastery of Submission : Inventions of Masochism - Noyes, John K. (John Kenneth), 1955- (Book collections on Project MUSE., 1997)
The evolution of the concepts is documented by masochistic scenes in literature from John Cleland's Fanny Hill through Sacher-Masoch's Venus in Furs and Pauline Reage's Story of O. Analysis of Freud's vastly influential rereading of masochism precedes an exploration of the work of his successors, including Wilhem Reich, Theodor Reik, Helene Deutsch, and Karen Horney. According to Noyes, the thematics of feminine masochism emerged only gradually from an exclusively male concept.